PENGKAJIAN KAPANG ENDOFIT DARI TAMAN NASIONAL GUNUNG HALIMUN SEBAGAI PENGHASIL GLUKOAMILASE - Ruth Melliawati; Ricky Setiadi Suherman; Bambang Subardjo (The East Java Biological Society, 2006)
Production of glucoamylase generally used through the fermentation-using microorganism. One of microorganism source which never been studied are from endophyte fungus. The purpose of this research is to study the potential microbes of Gunung Halimun Nasional Park (GHNP) for glucoamylase production. Thirty-seven isolate of endophyte fungi has been investigated for the ability of glucoamylase production on PSA (Potato starch agar) media with the strength of clear zone and colony. The potential isolates inoculated to Czapek media to produce glucoamylase on 50 ml scale and measured its activity every 24 hours of incubation time for 96 hours. The best isolate then was reproduced on the larger media (100 ml), and resumed with filtration and ultra-filtration. The enzyme activity, specific activity, and degree of protein was measured in every phase. Selection of amylolitic strength resulted that HL.110F.488 produced the highest amylolitic strength with halo size of 10.47 cm2, or equal with hydrolysis of starch of 0.0494 gram for 96 hours, while both isolate HL.44F.199 and HL.45F.205 had low amylolitic capacities but a very wide of colony growth, each 38.54 cm2 and 30.76 cm2. Isolat HL.44F.199 produced the highest enzyme activity of 5452.633 unit at 72 hours fermentation, while isolate HL.45F.205 with 4725.58 units at 72 hours fermentation and isolate HL.110F.488 with 3167.609 units at 96 hours fermentation. Glucoamylase has been reproduced by isolate HL.44F.199 on volume media 100 ml. The results show that enzyme activity is 4197.10 units with specific activity 2851.44 U/mg proteins, both get an increasing result after filtration and ultra-filtration reach out 5910.86 units and 4534.45 U/mg proteins.